DESIGN OF SHELL AND TUBE TYPE HEAT EXCHANGER FOR NANOFIBRIL CELLULOSE PRODUCTION PROCESS - Hanif Nur Purnamasari; Teguh Kurniawan; Asep Bayu Dani Nandiyanto (Universitas Komputer Indonesia, 2021)
Heat exchanger plays an important role in industry. In industrial applications, the type of heat exchanger that is often found is the shell and tube type heat exchanger. The aim of this paper is to of tube and shell type heat exchanger for nanofibril cellulose production applications. The method used is to design several assumptions and calculate parameters related to determining the performance of the heat exchanger. The parameters are calculated manually using the Microsoft Excel application. In this design, the TEMA standard is used as a reference. The result of this paper is the heat exchanger has 53 pcs of tubes with the effectiveness up to 89.21%. This indicates that the overall performance of the heat exchanger in cellulose nanofibril production applications can be further improved by selecting the right fluid, fluid flow rate, and other physical properties, as well as the number of tubes that will be required